Life Detail and Metaphorical Image Interpretation (Texas Journal of Multidisciplinary Studies, 2022)
In this article researched about the role and importance of metaphor in poetry, analyzed on the example of poems by the poetess Khalima Akhmedova. It is especially significant for the fact that metaphors drew the image of the lyrical hero in his psyche to scientific analysis.